2015
DOI: 10.1007/s40436-015-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vibration-assisted machining: principle, design and application

Abstract: Ultrasonic vibration-assisted (UVA) machining is a process which makes use of a micro-scale high frequency vibration applied to a cutting tool to improve the material removal effectiveness. Its principle is to make the tool-workpiece interaction a microscopically non-monotonic process to facilitate chip separation and to reduce machining forces. It can also reduce the deformation zone in a workpiece under machining, thereby improving the surface integrity of a component machined. There are several types of UVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(47 citation statements)
references
References 130 publications
2
32
0
Order By: Relevance
“…According to Eqs. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), the value of contact angle increases and the surface wettability turns to be more hydrophobic. In addition, it is reported that the contact angle is one of the important factors 16 indicating the surface free energy, where smaller surface free energy corresponds to higher contact angles [8].…”
Section: Wettability Testing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eqs. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), the value of contact angle increases and the surface wettability turns to be more hydrophobic. In addition, it is reported that the contact angle is one of the important factors 16 indicating the surface free energy, where smaller surface free energy corresponds to higher contact angles [8].…”
Section: Wettability Testing Resultsmentioning
confidence: 99%
“…As a new machining method, vibration assisted micro milling (VAMM), featuring a periodic separation between the workpiece and the tool, offers numerous advantages such as lower cutting force, longer tool life, better surface quality, and higher machining accuracy [16][17][18][19][20][21]. VAMM has found applications in processing hard and brittle materials such as silicon, titanium alloy and ceramics [22]. Moreover, with an appropriate selection of parameters, unique surface textures can be created by VAMM.…”
Section: Introductionmentioning
confidence: 99%
“…ductility, high tensile strength, micro-hardness, grain orientation, etc.) may change the overall machinability [20]. The current study presents an approach of applying ultrasonic vibration during the turning of Al alloys, thus, generating the UAT process.…”
Section: Experimental Descriptionmentioning
confidence: 99%
“…Micro-scale high frequency vibration with small amplitude is applied on the tool or workpiece to realize the tool-workpiece separation during the milling process. Several research studies have concluded that the tool-workpiece separation in ultrasonic vibration-assisted milling is the main reason for several benefits including improved surface quality [1], lower machining forces, and extended tool life [2]. This tool-workpiece interaction is microscopically non-monotonic which facilitates chip separation and therefore reduces machining forces.…”
Section: Introductionmentioning
confidence: 99%